2015
DOI: 10.1111/jar.12183
|View full text |Cite
|
Sign up to set email alerts
|

Structured Medication Review to Improve Pharmacotherapy in People with Intellectual Disability and Behavioural Problems

Abstract: This high prevalence of DRPs is worrying. The structured medication review is a valuable instrument to optimize pharmacotherapy and to support psychiatrists in adequate prescribing of both psychotropic and somatic drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(57 citation statements)
references
References 32 publications
3
53
1
Order By: Relevance
“…There is also significant variation in the reported prevalence of psychotropic polypharmacy, with prevalence rates reported from 22% to 40% (O'Dwyer et al 2017;Lunsky and Modi 2018). This is consistent with the range of reported psychotropic prescribing rates in the literature varying from 25% to 89% (Deb et al 2015; Scheifes et al 2016;Bowring et al 2017b). The high degree of reported variance in psychotropic prescribing rates and polypharmacy in general is a consequence of the heterogeneity of polypharmacy definitions (Masnoon et al 2017), weak analytical approaches (Stortz et al 2014) and convenience or clinic sampling being used in most studies (Haider et al 2014;Stortz et al 2014;Bowring et al 2017b).…”
Section: Introductionsupporting
confidence: 71%
See 2 more Smart Citations
“…There is also significant variation in the reported prevalence of psychotropic polypharmacy, with prevalence rates reported from 22% to 40% (O'Dwyer et al 2017;Lunsky and Modi 2018). This is consistent with the range of reported psychotropic prescribing rates in the literature varying from 25% to 89% (Deb et al 2015; Scheifes et al 2016;Bowring et al 2017b). The high degree of reported variance in psychotropic prescribing rates and polypharmacy in general is a consequence of the heterogeneity of polypharmacy definitions (Masnoon et al 2017), weak analytical approaches (Stortz et al 2014) and convenience or clinic sampling being used in most studies (Haider et al 2014;Stortz et al 2014;Bowring et al 2017b).…”
Section: Introductionsupporting
confidence: 71%
“…Given we found no significant relationship with a psychiatric diagnosis over the life course, it is theoretically possible that these classifications of drugs are prescribed in higher doses in response to other factors such as challenging behaviour. This 'off label' prescribing is a well-documented phenomenon with adults with ID (Gomes et al 2019;Perry et al 2018;Bowring et al 2017b;Scheifes et al 2016;Sheehan et al 2015;Deb 2015;Doan et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has indicated that individuals with ID and CB are prescribed with more psychotropic medications than those without CB [60][61][62][63][64][65][66][67], despite little evidence of clinical benefit [68][69][70] where mental health issues are not present. There are significant side effects of these medications with weight gain, somnolence, metabolic syndromes, and behavioural impacts being reported [66,[70][71][72][73][74]. High rates of psychotropic medication use (49% [23]; 38% [60]) are a major issue for people with ID and CB, and medication reduction should be a priority area for services.…”
Section: The Association Between Cb and Psychotropic Medicationmentioning
confidence: 99%
“…Fourthly, we represented the additional use of psychotropic medication as an outcome of CB and have included the effects of psychotropic medication as feeding back into additional vulnerability for CB. The physical and behavioural side effects described above [66,[70][71][72][73][74] may also have a cyclical impact on biological vulnerabilities for CB, hence we have included a feedback loop into biological vulnerabilty factors.…”
Section: A Revised Framework Model For Cbmentioning
confidence: 99%